Parenting pattern of feeding in stunting toddlers at the working area of Tegallalang I Primary Health Centre - Luh Gede Pradnyawati; Komang Triyani Kartinawati; Dewa Ayu Putu Ratna Juwita (Faculty of Medicine, Public Health, and Nursing, Universitas Gadjah Mada, 2019)
Stunting is a growth disorder that affects the measurements of Length-for-Age or Height-for-Age, which is characterized by a body condition that tends to be short. Children under five are categorized as short-bodied if the z-score is less than -2SD. In Indonesia, approximately 29% of children under five are included in the short-bodied category. A good nutritional intake at this time is a depiction of proper growth and development in the future. The health status of infants is related to parenting patterns of feeding. This study aimed to find out the description of parenting patterns of feeding in stunting toddlers in the working area of Tegallalang I Primary Health Centre. The study belongs to qualitative research with a phenomenological approach. The sample of this study was 5 mothers who had stunting toddlers. Data were collected by applying a purposive sampling technique. Data that had been collected consists of two types, i.e., primary data and secondary data. Data were analyzed using thematic analysis techniques. Some respondents had fed their toddlers with exclusive breastfeeding until they were 6 months old, but the frequency of feeding was ruled out. In addition, most respondents had only started to feed their babies with complementary food for breastfeeding at the time they were 6 months old. Still, they had not paid attention to their nutritional needs, the precise frequency of feeding, the kinds of better food for toddlers, and appropriate food variations. These results indicate that the wrong parenting pattern of feeding in children under five has the potential to cause stunting. Therefore, more attention to this matter is necessarily needed to reduce the severe incidence of stunting.